Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0168520
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Motor-Skill Acquisition Improves with Size of Self-Controlled Virtual Hands

Abstract: Visual feedback in general, and from the body in particular, is known to influence the performance of motor skills in humans. However, it is unclear how the acquisition of motor skills depends on specific visual feedback parameters such as the size of performing effector. Here, 21 healthy subjects physically trained to perform sequences of finger movements with their right hand. Through the use of 3D Virtual Reality devices, visual feedback during training consisted of virtual hands presented on the screen, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The intensity of the training seems important in this context as well; a previous study reported delayed gains in performance only once individual saturation within the initial training sessions had been achieved 45 . It has also been documented that feedback guidance helps to optimise motor performance and motor learning of jaw muscles 35,46,47 . It should be noted here that our study's oral motor task was quite demanding, requiring a high degree of oral sensorimotor control.…”
Section: Discussionmentioning
confidence: 67%
“…The intensity of the training seems important in this context as well; a previous study reported delayed gains in performance only once individual saturation within the initial training sessions had been achieved 45 . It has also been documented that feedback guidance helps to optimise motor performance and motor learning of jaw muscles 35,46,47 . It should be noted here that our study's oral motor task was quite demanding, requiring a high degree of oral sensorimotor control.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, left hand performance gain correlated with the neural activity during training (Ossmy and Mukamel, 2016 ). Thus, altering online visual feedback (for instance in terms of involved effector, its size, or movement pace) can boost motor performance and modulate cortical activity (Senna et al, 2015 ; Ossmy and Mukamel, 2016 , 2017a , b ). Similarly, in our study we found that online concurrent visual feedback improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…Here we extended the standard MVF approach by using visual feedback in a VR environment, which allows feedback to be controlled by software. Future studies using this environment can introduce various perturbations (in time and space, such as temporal delays or size changes in virtual hands 39 ) to find optimal parameters for efficient rehabilitation.…”
Section: Discussionmentioning
confidence: 99%